2017
DOI: 10.3233/bme-171661
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-frequency vibrations on blood flow improvement in human’s limbs

Abstract: The fundamental cause of diabetic limbs' problem is insufficient blood supply. The aim of the current work was to experimentally and numerically investigate the blood flow velocity and pressure changes in the channel during vibrational excitation. The micro-scale Particle Image Velocimetry (μPIV) technique as well as corresponding numerical channel model in COMSOL Multiphysics software were used to investigate the influence of external vibrations. Momentum upstream flow were noted on the fluid that was influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…20 Furthermore, prostaglandins are indicated to elevate blood flow during increased metabolic demands such as exercise. 5 Compression stockings, heat, massage, and vibration techniques are suggested to increase the blood flow and therefore might facilitate recovery after activity 17,23,38,49,50 ; however, further research is needed to investigate the vascular response of these techniques in the Achilles tendon since current literature is limited to changes in blood flow at the skin surface. Because the current study identified that the hazard for developing AT is higher when the increase in blood flow after running is lowered, further investigation is needed regarding the factors that influence this vascular response, such as smoking, body mass index, diabetes, tendon structure, high cholesterol levels, genetics, nutrition, and age.…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, prostaglandins are indicated to elevate blood flow during increased metabolic demands such as exercise. 5 Compression stockings, heat, massage, and vibration techniques are suggested to increase the blood flow and therefore might facilitate recovery after activity 17,23,38,49,50 ; however, further research is needed to investigate the vascular response of these techniques in the Achilles tendon since current literature is limited to changes in blood flow at the skin surface. Because the current study identified that the hazard for developing AT is higher when the increase in blood flow after running is lowered, further investigation is needed regarding the factors that influence this vascular response, such as smoking, body mass index, diabetes, tendon structure, high cholesterol levels, genetics, nutrition, and age.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that exposure to vibration or PT promotes an increased metabolic activity occurring within the muscles, including increased blood flow, 72 oxygen saturation 73 and temperature. 74 These acute physiological responses may be contributing to the positive muscle strength and explosive muscle strength results seen in this review.…”
Section: Metabolic Changes From Percussive Therapymentioning
confidence: 99%
“…By the end of 1970s, Broner (1978), in a publication in the Journal of Sound and Vibration, had already addressed the issue of low frequency noise (LFN) 8 as a topic of growing interest in the society at the time. Currently, studies show that low frequency can influence physical and mental health in varied ways (Ferreira et al, 2006;Pedersen, 2008;Broner, 2011;Nohama & Silvério-Lopes, 2009;Venslauskas, Ostasevicius, & Vilkinis, 2017). In fact, researches with infrasound, ultrasounds and low frequency sounds are recent in several aspects.…”
Section: Introductionmentioning
confidence: 99%